2006
DOI: 10.1080/13576280600783679
|View full text |Cite
|
Sign up to set email alerts
|

Development of the community-oriented medical education curriculum of Pakistan: A case report on the national initiative on curriculum development

Abstract: KEYWORDS Curriculum development, problem-based learning, community oriented medical education, change management, faculty training. BackgroundThe medical curriculum in Pakistan includes the following courses: anatomy, physiology, and biochemistry. These courses are offered in the first two years using lectures, tutorials and laboratory work. In the last three years, pathology, pharmacology, forensics and community medicine courses are taught by using clerkships in medicine, surgery, pediatrics, gynecology, obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…A study conducted to assess the satisfaction of medical students in three public medical colleges in Karachi has shown that more than half of the senior medical students were not satisfied with the knowledge and skills gained in courses, including Behavioral Sciences and Pediatrics (Aziz et al 2006). All this evidence suggests that most GPs in Pakistan do not receive adequate training in child and adult psychiatry and neurology (Baig et al 2006;Gadit 2008;Usman 2009;Wasay 2003). Psychiatry training is an important component of the medical curriculum (Walton and Gelder 1999).…”
Section: Medical School Curriculummentioning
confidence: 96%
“…A study conducted to assess the satisfaction of medical students in three public medical colleges in Karachi has shown that more than half of the senior medical students were not satisfied with the knowledge and skills gained in courses, including Behavioral Sciences and Pediatrics (Aziz et al 2006). All this evidence suggests that most GPs in Pakistan do not receive adequate training in child and adult psychiatry and neurology (Baig et al 2006;Gadit 2008;Usman 2009;Wasay 2003). Psychiatry training is an important component of the medical curriculum (Walton and Gelder 1999).…”
Section: Medical School Curriculummentioning
confidence: 96%
“…They were Dow Medical College (Sindh), King Edward Medical College (Punjab), Bolan Medical College (Balochistan) and Ayub Medical College (Khyber Pakhtoon Khwah). The faculty of medical colleges and the other stake holders (medical students, representatives of ministry of health and service providers from potential catchment areas who were to become partners in student learning) were involved in revising the traditional curriculum with incorporation of COME in undergraduate teaching [5]. Medical students were also involved in this process and participated in the introductory curriculum development workshops which introduced the participants to the educational principles and PBL process.…”
Section: Introductionmentioning
confidence: 99%
“…A consensus was reached by the faculty of COME colleges in the initial workshops that the medical graduate should be a safe, skillful, and humane medical practitioner [5]. The curriculum was distributed over five years in three phases with horizontal and longitudinal blocks as follows:…”
Section: Introductionmentioning
confidence: 99%
“…In Pakistan, CBE has existed for over 25 years and accredited medical and nursing schools are required to include some form of CBE in their curricula [15]. However, our findings demonstrate that there are a number of challenges that must to be addressed to truly integrate CBE as an educational approach within HPE.…”
Section: Discussionmentioning
confidence: 95%
“…Of the participants in our study more than half were not formally trained for CBE, moreover a large number of participants did not appear to have internalised the real meaning of CBE, with many concepts and competencies unclear. Lubna et al, reported similar results that “unfortunately due to lack of commitment from administration, communication amongst stakeholders and faculty buy in CBE could not be effectively implemented in Pakistan” [15]. …”
Section: Discussionmentioning
confidence: 99%